Diversity of Nicotinic Acetylcholine Receptor Positive Allosteric Modulators Revealed by Mutagenesis and a Revised Structural Model - Newcombe, Joseph (Mol Pharmacol, 2018)
By combining electrophysiological and computational approaches we have examined a series of positive allosteric modulators (PAMs) acting on the human α7 nicotinic acetylcholine receptor (nAChR). Electrophysiological studies have focused on three α7-selective PAMs (A-867744, TBS-516, and TQS) that display similar effects on wild-type α7 nAChRs. In addition to potentiating agonist-evoked responses, all three compounds reduce receptor desensitization and, consequently, are classed as type II PAMs. Despite having similar effects on wild-type receptors, A-867744 was found to have profoundly differing effects on mutated receptors compared with TBS-516 and TQS, a finding that is consistent with previous studies indicating that A-867744 may have a different mechanism of action compare with other α7-selective type II PAMs. Due to evidence that these PAMs bind within the α7 nAChR transmembrane region, we generated and validated new structural models of α7. Importantly, we have corrected a previously identified error in the transmembrane region of the original cryo–electron microscopy Torpedo model; the only pentameric ligand-gated ion channel imaged in a native lipid membrane. Real-space refinement was used to generate closed and open conformations on which the α7 models were based. Consensus docking with an extended series of PAMs with chemical similarity to A-867744, TBS-516, and TQS suggests that all bind to a broadly similar intersubunit transmembrane site. However, differences in the predicted binding of A-867744, compared with TBS-516 and TQS, may help to explain the distinct functional effects of A-867744. Thus, our revised structural models may provide a useful tool for interpreting functional effects of PAMs.